(untitled) (Scientific journal of the Fergana State University, 2024)
This article talks about the important role of forming the pedagogical skills of a teacher today, and the richer the culture of speech in the pedagogical skills of a teacher, the deeper his knowledge, thinking, scientific worldview, thoughts and observations will be. This article also describes in detail the pedagogical abilities of the teacher, the possibilities of his development and use in order to improve the quality of education.